Kontektualisasi Direct Instruction Dalam Pembelajaran Sains - Zahriani, Zahriani (Lantanida Journal, 2014)
Direct Instruction is one teacher teaching model is centered on the center or teacher. This learning model emphasizes the delivery of content is done verbally by the teacher to the learner. In the implementation of this model has the characteristic form of the five phases of a very important activity in the form of submission of the learning objectives, demonstrate knowledge and skills, guiding the training, checking understanding and provide feedback and provide advanced training and implementation. Research conducted on the use of the model of Direct Instruction in science learning so far shown significant results to increase students' understanding of science concepts. Direct Instruction is still relevant models used to study the science of materials that explain concepts and procedural and can be combined with other learning models, the use of the media is to help the implementation of the Direct Instruction model study